Metodología para la clasificación geomorfológica de los cursos fluviales de la cuenca del Ebro - Díaz Bea, Elena; Ollero Ojeda, Alfredo (Geographicalia, 2016)
A new classification of stream channels is established from geomorphological features (channel slope, channel pattern, valley morphology), which has been applied to the fluvial hydrosystems of the Ebro basin, in order to get some fluvial reaches, functionally homogenous, to be the base for the WaterFramework Directive (2000/60/EC). As a result, the river network of the Ebro basin has been divided into 1.436 fluvial reaches, and 78 types of fluvial channels have been distinguished, which can be grouped into elementary (32), of transition (25) and very modified (21). Finally, some general proposals are suggested for its future management, particularly for the elementary types of streain channel, which represent the 83,5% of the total number of fluvial reaches.